Estratégia de monitoramento em apoio ao licenciamento ambiental em trecho de vazão reduzida - Silva, Regis Leandro Lopes da (2012)
In the environmental licensing of hydroelectric plants are prescribed streamflow should be maintained downstream of the dam, but these flows often cannot ensure the maintenance of water quality for the stretch. The aim of this study is to present a robust and expeditious strategy of water quality monitoring. This strategy is developed for supporting the stipulation of flow regime in reduced flow reach (RFR) by dams. The Hydropower plant Passo São João (HPP PSJ) in Rio Ijuí-RS was used as study case. This Hydropower is a power plant without storage capacity presenting a RFR of 4 km. The monitoring for collecting water quality data is made by using a multiparameter probe and laboratory analysis. It is used ten monitoring points along the Rio Ijuí, two of them located in the RFR. Correlations between data obtained with a multiparameter probe and data determined in the laboratory are made to evaluate the application of the probe. Complementing the study, the HPP PSJ is contextualized according to the impact on water quality in the Rio Ijuí, tracing a longitudinal profile of dissolved oxygen (DO) along with the evaluation of the direct contribution by RFR comparison of flows. Moreover, the variability of DO concentrations in sections monitoring RFR is evaluated considering the determinations along the section. Those sections are associated with flow velocity profiles that were determined by the Acoustic Doppler Current Profiler (ADCP). The correlations between the curves of monitoring data and curves from the extraction of data - at different frequencies - are developed for determining the optimal monitoring frequency. The comparison between measurements with the probe and measurements in the laboratory are satisfactory, presenting similar values for most parameters. The layout of the longitudinal profile of the DO concentrations demonstrates the strong influence of the HPP PSJ structures in dam downstream DO level, reinforcing the need for a monitoring strategy. However the effect of reducing inflow in the dilution charges has not been noted in view of the minimum incremental area flow. Near riverbank measurements were representative, since the variability of measurements along the section generally was less than 2% on average. Finally the ideal frequency obtained with the correlation curves for different frequencies is four days for both points of RFR. The overall conclusion of this study is to propose a monitoring strategy based on using a multiparameter probe in which the operator formulates the determinations near the riverbank with a monitoring frequency of four days, taking as basis the representative parameter the dissolved oxygen for this case.